E do silêncio fez-se a fala: oralidade e trajetória de vida de mulheres negras da cidade de Sorocaba - Pereira, Marco Antonio (2014)
This work aimedat analyzing the life trajectory of black women in the city of Sorocaba from the perspective of their race and gender. Itseeks to investigate the role of militancy in thedevelopment oftheir political conscience and how this militancy can be understood as an educational power. The methodologyusedwas that oforal history and, in this context, the analysis is focused in the narrator’s experienced subjectivity. Analysis categories were established from the recurrence observed in their speech. Our approach consists in establishing how these women experienced their own history rather than discovering new historical facts. In orderto conduct the analysis, we gathered aspects that were recurrent both in the interviewees’ speeches and in the forms of resistance adopted by the black people as captive, freedmen or in the post-abolition period. Among the forms of resistance adopted by these women, associations, familiar structure, scholar process and Clube 28 de Setembroas a place for racial assertion are recurrent. We were able to establish that they were all strengthened as black women by the militancy process. Finally, more than never, from my positionas a man speaking aboutour interviewees’ lives, I was able to understand how much we can learn from ourYalodes,ourwise women.